STUDY OF RESILIEN MODULUS IN MIXING ASPHALT CONCRETE (AC-BC) BINDING LAYER WITH BOTON ASPHALT GRANULAR - Jerry (NIM 25006309), Alfin
ABSTRACT: The needs of asphalt in road construction increase every year. Most of the asphalt demand was fulfilled by importing. Local product, such as Buton`s asphalt in Sulawesi Tenggara, could be a solution in decreasing the asphalt import. The objective of this research is to study the Resilient Modulus of Asphalt Concrete Binder Course (AC-BC) using BGA type 15/20 Lawele. The study is based on the New Specification of Hot Mix Asphalt 2007 and the PRD method. All type of asphalt mix at OBC were evaluated to Water Endurance and stiffness modulus UMATTA. There are four types of asphalt mix are used in this research, i.e. without BGA (BGA-0), 4% substitution BGA (BGA-4), 8% substitution BGA (BGA-8) and 12% substitution BGA (BGA-12) from total weight of mixes. Each level of BGA substitution will make contribution to the aggregate, thus will change the whole aggregate gradation. For BGA-0, BGA-4, BGA-8, and BGA-12 mixes the OBC were 5.84%, 6.20%, 6.98%, and 7.30%. The IKS are 84.40%, 92.39%, 92.61%, and 92.82%. Marshall Stability were 990.11 Kg, 1087.25 Kg, 1171.37 Kg, and 1132.89 Kg. Stiffness modulus in 35 degrees C are 884.7 Mpa, 912.8 Mpa, 809.3 Mpa, and 708.6 Mpa. In 45 degrees C the stiffness modulus are 354.4 Mpa, 331.1 Mpa, 361.9 Mpa, and 385.4 Mpa. It is clear that stiffness modulus will increase as BGA increases for certain temperature. The higher temperature and BGA contents, the higher stiffness modulus will be. At temperature of 45 degrees C , BGA bitumen was melt so that the asphalt and aggregate will fill and bond each other. Different results was obtained in Stiffness Modulus between the Shell and Nottingham method, this is caused by the different parameter used in those formula. Concluding this research, BGA substitution indicates the increasing performance of the mix and its stiffness modulus. So that a research result with 8 % BGA substitution is recommended.